A descriptive study to assess the knowledge of staff nurses regarding antibiotic resistance at a selected hospital, Bangalore - Sasmal, Romashree; N., Vanitha; Das, Saheli; Sarkar, Shreya; Guchait, Somashri; Das, Soumya; Chakraborty, Sulagna; Shinglai, Wonmila (International Journal of Basic & Clinical Pharmacology, 2026)
Background: Antibiotic resistance is a major global health problem that compromises the effective treatment of infectious diseases. Nurses play a crucial role in administration of antibiotic and monitoring therapeutic outcome. Proper knowledge among nurses can help reduce the misuse of antibiotics and prevent the development of resistance organism. This study conducted with the objective to assess level of knowledge about antibiotic resistance among staff nurses and to find association between knowledge of staff nurses regarding antibiotic resistance with sociodemographic variables Methods: We conducted a descriptive cross-sectional study in the month of November 2025 using non-probability convenience sampling among 402 staff nurses at a selected hospital in Bangalore, data was collected through Google form with structured questionnaire and analyzed using descriptive and inferential statistics. Results: Among all the participants 17.7% had adequate knowledge, 46.3% had moderately adequate knowledge, 36% had inadequate knowledge of antibiotic resistance. The mean score was 5 with standard deviation of ±4.820. There is significant association between knowledge of staff nurses regarding antibiotic resistance with area of work only (chi square value=13.100, p=0.041). Conclusions: The findings revealed that most of the staff nurses had moderately adequate knowledge. To improve nurses’ knowledge, periodic assessment should be conducted to identify their learning needs. It will assist in planning and developing formal educational and training programs to enhance nurses understanding of antibiotic resistance.